Comparison of SNP Variation and Distribution in Indigenous Ethiopian and Korean Cattle (Hanwoo) Populations - Zewdu Edea; Hailu Dadi; Sang Wook Kim; Tadelle Dessie; Kwan-Suk Kim (Genomics & Informatics)
Although a large number of single nucleotide polymorphisms (SNPs) have been identified from the bovine genome-sequencing project, few of these have been validated at large in Bos indicus breeds. We have genotyped 192 animals, representing 5 cattle populations of Ethiopia, with the Illumina Bovine 8K SNP BeadChip. These include 1 Sanga (Danakil), 3 zebu (Borana, Arsi and Ambo), and 1 zebu × Sanga intermediate (Horro) breeds. The Hanwoo (Bos taurus) was included for comparison purposes. Analysis of 7,045 SNP markers revealed that the mean minor allele frequency (MAF) was 0.23, 0.22, 0.21, 0.21, 0.23, and 0.29 for Ambo, Arsi, Borana, Danakil, Horro, and Hanwoo, respectively. Significant differences of MAF were observed between the indigenous Ethiopian cattle populations and Hanwoo breed (p < 0.001). Across the Ethiopian cattle populations, a common variant MAF (≥0.10 and ≤0.5) accounted for an overall estimated 73.79% of the 7,045 SNPs. The Hanwoo displayed a higher proportion of common variant SNPs (90%). Investigation within Ethiopian cattle populations showed that on average, 16.64% of the markers were monomorphic, but in the Hanwoo breed, only 6% of the markers were monomorphic. Across the sampled Ethiopian cattle populations, the mean observed and expected heterozygosities were 0.314 and 0.313, respectively. The level of SNP variation identified in this particular study highlights that these markers can be potentially used for genetic studies in African cattle breeds.